A human protein related to yeast Cdc6p - Williams, R. Sanders (The National Academy of Sciences of the USA, 1997)
The unstable proteins Cdc6p and cdc18(+) are essential and rate limiting for the initiation of DNA replication in Saccharomyces cerevisiae and Schizosaccharomyces pombe, respectively, and also participate in checkpoint controls that ensure DNA replication is completed before mitosis is initiated. We have identified Xenopus and human proteins closely related to Cdc6p/cdc18. The human protein, p62(cdc6), is encoded on chromosome 17q21.3 and includes putative cyclin-dependent kinase phosphorylation sites, destruction boxes, a nucleotide binding/ATPase domain, and a potential leucine zipper. Expression of p62(cdc6) mRNA and protein is suppressed in human diploid fibroblasts made quiescent by serum starvation, and peaks as cells reenter the cell cycle and replicate DNA following serum stimulation. Conservation of structure among proteins involved in initiation suggests that fundamental features of replication complexes are maintained in all eukaryotes.